2018
DOI: 10.5210/ojphi.v10i1.8829
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Surveillance of Heat-Related Illness in Pinal County

Abstract: ObjectiveUsing a syndromic surveillance system to understand the magnitude and risk factors related to heat-related illness (HRI) in Pinal County, AZ.IntroductionExtreme heat is a major cause of weather-related morbidity and mortality in the United States (US).1 HRI is the most frequent cause of environmental exposure-related injury treated in US emergency departments.2 More than 65,000 emergency room visits occur for acute HRI each summer nationwide.3 In Arizona, HRI accounts for an estimated 2,000 emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Improvements to the process for HRI surveillance and case interviews has helped PCPHSD to more effectively identify and assess HRI cases. Utilizing two ESSENCE queries assisted with HRI case identification, and improvements to the case contact protocol and interview questionnaire increased response rate from 25% in 2017 [3] to 53.2% in 2018. Other improvements included the use of follow-up text messaging and Spanish text/interview options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements to the process for HRI surveillance and case interviews has helped PCPHSD to more effectively identify and assess HRI cases. Utilizing two ESSENCE queries assisted with HRI case identification, and improvements to the case contact protocol and interview questionnaire increased response rate from 25% in 2017 [3] to 53.2% in 2018. Other improvements included the use of follow-up text messaging and Spanish text/interview options.…”
Section: Discussionmentioning
confidence: 99%
“…Pinal County, which has an estimated population of 430,237 individuals [2], contributes to the number of HRI visits to Arizona Emergency Departments that occur each year. In order to determine the burden of HRIs within the county, Pinal County Public Health Services District (PCPHSD) began to conduct heat-related illness surveillance in 2017 and found that 149 HRI cases had been reported that year [ 3 ] . PCPHSD continued to conduct HRI surveillance through summer 2018 to build on surveillance activities from 2017 and meet the following goals:…”
Section: Introductionmentioning
confidence: 99%
“…Rising temperatures due to climate change and extreme heat is a major concern for human health in the United States (US) Southwest and particularly in Arizona [1] , [2] , [3] , [4] . Four health departments (Pima County Health District, Yuma County Public Health Services District, Maricopa County Department of Public Health, and Pinal County Public Health Services District) along with the Arizona Department of Health Services (ADHS) participate with the Centers for Disease Control and Prevention's Climate-Ready States and Cities Initiative which implements the Building Resilience Against Climate Effects (BRACE) Framework as part of the program to plan for heat (among other climate hazards) and subsequent heat-related illness (HRI) within their jurisdiction [5] , [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently these health departments conduct active surveillance to monitor and track HRI in their jurisdiction. Collecting HRI data is a labor-intensive activity that takes considerable public health staff time, including data extraction, reviewing medical records, and syndromic surveillance [ 3 , 8 , 9 ]. As such, there can be a delay of 3-4 months between preliminary counts and final values, and summaries of HRI morbidity and mortality can take up to a year for final approvals in local health departments.…”
Section: Introductionmentioning
confidence: 99%